Green innovation in China : China's wind power industry and the global transition to a low-carbon economy - Lewis, Joanna I. (Contemporary Asia in the world., 2013)
As the greatest coal producing and consuming nation in the world, China would seem an unlikely haven for wind power. Yet the country now boasts a world-class industry that promises to make low-carbon technology more affordable and available to all. Conducting an empirical study of China's remarkable transition and the possibility of replicating their model elsewhere, Joanna I. Lewis adds greater depth to a theoretical understanding of China's technological innovation systems and the country's current and future role in a globalized economy. Lewis focuses on China's specific methods.